Alteration in Marrow Stromal Microenvironment and Apoptosis Mechanisms Involved in Aplastic Anemia: An Animal Model to Study the Possible Disease Pathology - Sumanta Chatterjee; Ranjan Kumar Dutta; Pratima Basak; Prosun Das; Madhurima Das; Jacintha Archana Pereira; Malay Chaklader; Samaresh Chaudhuri; Sujata Law (Hindawi Limited, 2010)
Aplastic anemia (AA) is a heterogeneous disorder of bone marrow failure syndrome. Suggested mechanisms include a primary stem cell deficiency or defect, a secondary stem cell defect due to abnormal regulation between cell death and differentiation, or a deficient microenvironment. In this study, we have tried to investigate the alterations in hematopoietic microenvironment and underlying mechanisms involved in such alterations in an animal model of drug induced AA. We presented the results of studying long term marrow culture, marrow ultra-structure, marrow adherent and hematopoietic progenitor cell colony formation, flowcytometric analysis of marrow stem and stromal progenitor populations and apoptosis mechanism involved in aplastic anemia. The AA marrow showed impairment in cellular proliferation and maturation and failed to generate a functional stromal microenvironment even after 19 days of culture. Ultra-structural analysis showed a degenerated and deformed marrow cellular association in AA. Colony forming units (CFUs) were also severely reduced in AA. Significantly decreased marrow stem and stromal progenitor population with subsequently increased expression levels of both the extracellular and intracellular apoptosis inducer markers in the AA marrow cells essentially pointed towards the defective hematopoiesis; moreover, a deficient and apoptotic microenvironment and the microenvironmental components might have played the important role in the possible pathogenesis of AA.